2010
DOI: 10.1080/09511921003642121
|View full text |Cite
|
Sign up to set email alerts
|

A review of machining feature recognition methodologies

Abstract: In a continuing quest to decrease the time interval between conceptualisation of a product and its first production, the use of information technology in design, analysis and manufacturing practice has been actively researched. The design engineer designs a part and sends the final design to the manufacturing engineer, who re-interprets the design and plans the manufacturing activities to produce the part. These two sections generally work in isolation from each other, resulting in high lead-time, duplication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 91 publications
0
36
0
1
Order By: Relevance
“…The recognised cylindrical-and conical-based features are very useful for process planning. A more comprehensive review about feature recognition can be found in a recent study by Verma and Rajotia (2010).…”
Section: Feature Recognition From Free-form Surface Modelmentioning
confidence: 99%
“…The recognised cylindrical-and conical-based features are very useful for process planning. A more comprehensive review about feature recognition can be found in a recent study by Verma and Rajotia (2010).…”
Section: Feature Recognition From Free-form Surface Modelmentioning
confidence: 99%
“…At the design phase, the manufacturing parameters of features can be gotten by the method of feature mapping from design parameters (Dong and Vijayan 1997;Lin, Lin, and Cheng 1997;Nagarajan and Reddy 2010;Verma and Rajotia 2010). SEC j (Specific energy consumption) is the energy consumption of removing per unit material in the jth process.…”
Section: Estimation Of Theoretical Cutting Energy Consumption Of a Fementioning
confidence: 99%
“…rozpoznawanie cech w komercyjnych systemach CAM Dostępnych jest szereg metod rozpoznawania cech technologicznych [1][2][3][4]. Producenci systemów CAM nie informują o wybranej metodzie rozpoznawania.…”
unclassified